SGLT2 inhibitors and cardiovascular outcomes in heart failure with mildly reduced and preserved ejection fraction: A systematic review and meta-analysis - Mainak Banerjee; Rimesh Pal; Kirthana Nair; Satinath Mukhopadhyay (Indian Heart Journal, 2023)
Aim: To provide a pooled effect of sodium-glucose cotransporter-2 inhibitors (SGLT2i) on cardiovascular outcomes in patients with heart failure with preserved ejection fraction (HFpEF: ≥50%) or/and mildly reduced EF (HFmrEF: 41–49%) regardless of baseline diabetes. Methods: We systemically searched PubMed/MEDLINE, Embase, Web of Science databases and clinical trial registries using appropriate keywords till August 28, 2022, to identify randomized controlled trials (RCTs) or post-hoc analysis of RCTs, reporting cardiovascular death (CVD) and/or urgent visits/hospitalization for heart failure(HHF) in patients with HFmrEF/HFpEF receiving SGLTi vs. placebo. Hazard ratios (HR) with 95% confidence intervals (CI) for outcomes were pooled together using generic inverse variance method with fixed-effects model. Results: We identified six RCTs, pooling data retrieved from 15,769 patients with HFmrEF/HFpEF. Pooled analysis showed that compared to placebo, SGLT2i use was significantly associated with improved CVD/HHF outcomes in HFmrEF/HFpEF (pooled HR 0.80, 95% CI: 0.74, 0.86, p < 0.001, I2 = 0%). When separately analyzed, benefits of SGLT2i remained significant across HFpEF (N = 8891, HR 0.79, 95% CI: 0.71, 0.87, p < 0.001, I2 = 0%) and HFmrEF (N = 4555, HR 0.77, 95% CI: 0.67, 0.89, p < 0.001, I2 = 40%). Consistent benefits were observed also in HFmrEF/HFpEF subgroup without baseline diabetes (N = 6507, HR 0.80, 95% CI: 0.70, 0.91, p < 0.001, I2 = 0%). Sensitivity analysis including the DELIVER and EMPEROR-Preserved trials found a trend towards significant beneficial effects on CV deaths with no heterogeneity (HR 0.90, 95% CI: 0.79, 1.02, p = 0.08, I2 = 0%). Conclusions: This meta-analysis established the place of SGLT2i as a foundational therapy among patients with HF with preserved and mildly reduced EF regardless of diabetes.